RANCANG BANGUN MODEL KEMITRAAN SINERGIS DALAM PENGEMBANGAN KLASTER AGRIBISNIS KENTANG - Hakim, Lukman; Sutami, Ni Putu (Jurnal Ilmu-Ilmu Pertanian, 2017)
The objectives of this study are to design a model of synergistic partnership in cluster development of potato agribusiness in an effort to increase revenue and bargaining position of farmers in Aceh Province. System dynamics methodology was applied, a modelling approach based on systemic thinking and a perspective based on feedback information as well as delays to understand the complex dynamic behaviour of physical, biological, and social systems on the agribusiness cluster of potato. Potato production centres in Aceh Province, namely Central Aceh and Bener Meriah, were chosen to be the working area of the study. Identification of the need for synergistic partnership model done through literature and interviews with experts from stakeholders, namely practitioners and policy makers involved in the procedure of input supply, production, and marketing of potato output. Data collected consisted of primary and secondary data. The primary data obtained through observation, in-depth interviews with respondents, as well as the activity of Focus Group Discussion, while secondary data obtained through the study of literature from various sources of literature, books, scientific journals, and a variety of publications related to this research. Formulation of the models was conducted by using Vensim DSS Software, followed by simulation. The result of this study indicated the role of three major scenarios which were important to design a model of synergistic partnership in cluster development of potato agribusiness in Aceh Province, those were: (1) the scenario of shortening the payment receivables interval of farmers and cooperatives, which showing the increasing of cash amount, (2) the scenario of designing model of synergistic partnership through the addition of loan funds and the elimination of receivables structure, resulting in the increasing number of revenues, profits, R/C, and cash, (3) the scenario of doing certification to the potato from synergistic partnerships farmers, showing the increasing of acceptance, profitability, R/C, and cash. To design a model of synergistic partnership in cluster development of potato agribusiness is a model of innovation and institutional management, which can accelerate the development of potato commodity, increase revenue and bargaining position of farmers, as well as accelerating economic growth in the region.